The Origin of Geothermal Water Around Slamet Volcano - Paguyangan - Cipari, Central Java, Indonesia - Sachrul Iswahyudi; Indra Permanajati; Rachmad Setijadi; Januar Aziz Zaenurrohman; Muhamad Afirudin Pamungkas (UIR PRESS, 2020)
The existences of several hot springs between Slamet volcano, Paguyangan, and Cipari Districts raised questions regarding their origin. Several studies have been conducted related to the hydrothermal system at the location. Subsequent studies are needed to understand the hydrothermal system at the research site for the sustainability and conservation of geothermal natural resources. This research has reviewed several previous studies plus the latest information on the origin of hot spring water with the help of deuterium (2H) and 18O isotopes. This study used geochemical analysis of hot springs (geothermal) and local meteoric water to obtain information on isotope values. This was used for the interpretation of the origin of geothermal water. This study also used regional geological analysis methods for the interpretation of the mechanism for the emergence of these hot springs. The results of the analysis informed that the origin of hot water was local meteoric water. The geological structure was weak enough to allow water from the geothermal reservoir to reach the surface and meteoric water into the reservoir.